PEMBUATAN GENTENG DI DESA PEJATEN DALAM FOTOGRAFI DOKUMENTER - Nariani, Ni Putu Lita; Raharjo, Anis; Candrayana, Ida Bagus (Retina Jurnal Fotografi, 2021)
The creator was interested in bringing up the theme of Making Tiles in Pejaten Village in Documentary Photography because of the modern roof tiles from outside Bali which could be a threat from the existence of pejaten tiles. Pejaten Village has been famous for its tile making from the past until now. Pejaten tile has a characteristic that is on the tile product there is the name "Pejaten" which is made with a direct printing technique from a tile mold made with a press. The purpose of this creation is to document the making of pejaten roof tiles in documentary photography. In the process of creating this photographic work, the creator uses the method of creation, namely direct observation by visiting the tile craftsmen in Pejaten Village and conducting interviews to find out how the roof tiles are made in Pejaten Village and the creator also observes the condition and situation of the object to be photographed and The creator applies several photography techniques into his photo works such as stop action, framing, point of view and lighting. The result of this creation is documentary photography which contains about the making of roof tiles starting from the selection of materials, mixing materials, printing, drying and finally the existence of making roof tiles in Pejaten Village is very important for the people there because the majority of the people there work as tile craftsmen and earn wages/salaries from selling. rooftile. Through documentary photography, it is hoped that it will be able to document the manufacture of roof tiles in Pejaten Village so that the existence of roof tiles in Pejaten Village is preserved in the form of documentary photography. Keywords: Tile Making, Pejaten Village, Documentary Photography